Layers of Nanocrystalline SiC as a New Type of Solid-State Hydrogen Storage - A. Guglya; A. Kalchenko; E. Lyubchenko; Yu. Marchenko; A. Semenov (Journal of Nanotechnology)
This paper presents the results related to the investigation of layers of nanocrystalline silicon carbide (nc-SiC) obtained by direct ion deposition for the purpose of hydrogen accumulation. The parameters of the production process providing the largest amount of accumulated hydrogen (more than 5.5 wt.%) were determined based on the mass spectrometric data on the desorption of atomic and molecular hydrogen from nc-SiC films. Electron microscopic examination revealed the structural features that are responsible for absorption, retention, and desorption of hydrogen at relatively low temperatures and pressures. The study results suggest that the main structural elements acting as the hydrogen traps are the vacant positions of carbon in nc-SiC. The presence of a developed system of intercrystalline boundaries in investigated films promotes the hydrogen desorption at relatively low temperatures.